2022
DOI: 10.3390/app12157759
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability in Automated Emotional Facial Expression Analysis: Exploring FaceReader 8.0 on Data from Typically Developing Children and Children with Autism

Abstract: Automated emotional facial expression analysis (AEFEA) is used widely in applied research, including the development of screening/diagnostic systems for atypical human neurodevelopmental conditions. The validity of AEFEA systems has been systematically studied, but their test–retest reliability has not been researched thus far. We explored the test–retest reliability of a specific AEFEA software, Noldus FaceReader 8.0 (FR8; by Noldus Information Technology). We collected intensity estimates for 8 repeated emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Instead, we used automated facial expression analysis to measure changes in the outward appearance of an individual's face, while not necessarily coinciding with an individual's subjective experiences, to explore the degree to which those expressions are transmitted even across the "obstacle" of a digitally mediated social interaction. Further, recent validation studies (see Dupré et al, 2020 for an overview) reported that automatic facial expression analysis algorithms offer sufficiently high reliability in comparison to human FACS coders (Höfling et al, 2022;Küntzler et al, 2021;Skiendziel et al, 2019;Stöckli et al, 2018) and to itself when measured at two measurement points (Borsos et al, 2022). In that sense, we conclude that facial expressions -independent of the underlying emotional state -represent highly relevant nonverbal cues and a channel for the interpersonal communication of subjective emotional experiences that can be reliably assessed using automated facial expression analysis.…”
Section: Limitationssupporting
confidence: 55%
“…Instead, we used automated facial expression analysis to measure changes in the outward appearance of an individual's face, while not necessarily coinciding with an individual's subjective experiences, to explore the degree to which those expressions are transmitted even across the "obstacle" of a digitally mediated social interaction. Further, recent validation studies (see Dupré et al, 2020 for an overview) reported that automatic facial expression analysis algorithms offer sufficiently high reliability in comparison to human FACS coders (Höfling et al, 2022;Küntzler et al, 2021;Skiendziel et al, 2019;Stöckli et al, 2018) and to itself when measured at two measurement points (Borsos et al, 2022). In that sense, we conclude that facial expressions -independent of the underlying emotional state -represent highly relevant nonverbal cues and a channel for the interpersonal communication of subjective emotional experiences that can be reliably assessed using automated facial expression analysis.…”
Section: Limitationssupporting
confidence: 55%
“…Recordings with a resolution of 640 × 480 at 33 frames per second were saved as MP4 files and analyzed frame by frame by FaceReader 8.1, an automated facial expression analysis software, a reliable and valid method for analyzing facial expression data (Noldus Information Technology, Wageningen, The Netherlands) 39 , 40 . FaceReader was set to detect each of the twenty most common facial Action Units (AUs), which were reported on a scale between 0 (not present) and 1 (maximally present).…”
Section: Methodsmentioning
confidence: 99%
“…From a measurement perspective, some studies have raised concern about the reliability of the software's emotion estimates. Borsos et al (2022) evaluated the test-retest reliability of emotion API and found small but significant differences in the ratings. Flynn et al (2020) observed group differences in the accuracy of emotion estimates between children and adults.…”
Section: Current Applications Of Emotion Recognition Apimentioning
confidence: 99%